Zooplankton of Deriner Dam Lake (Artvin-Türkiye) - Bulut, Hilal; Fidan, Dilek; Saler, Serap (My University, 2024)
This study was carried out seasonally at 8 stations determined in Deriner Dam Lake between 2020 and 2021. In order to determine the seasonal zooplankton taxon diversity and richness at the determined stations, the samples were collected in the surface water with a plankton net with a mesh size of 55 µm. In the distribution of zooplankton, more taxon was recorded in autumn and spring seasons compared to other seasons in terms of both the number of species and the number of individuals. In addition to presence of Rotifera species in high numbers in general, Polyarthra dolichoptera is the most common species seen in all seasons. Asplanchna sieboldi from Rotifera, Acanhopdiaptomus denticornis from Copepoda, and Daphnia cucullata from Cladocera were the dominant species of their groups.
Keywords: Cladocera; Copepoda; Rotifera